Scientific aspects of dialysis therapy - Congress International Society of Blood Purification 2016 : Hiroshima, Japan); Kawanishi, Hideki; Takemoto, Yoshiaki; Annual Meeting of Japanese Society for Dialysis Therapy 2016 : Osaka, Japan) (Basel : Karger, 2017)
This book brings together papers presented both during the 61st Annual Meeting of the Japanese Society for Dialysis Therapy (JSDT) and the 34th Congress of the International Society of Blood Purification (ISBP), held in Osaka in June and in Hiroshima in September 2016, respectively. They cover a broad spectrum of topics, ranging from hemodialysis, peritoneal dialysis, hemodiafiltration and technical innovations in blood purification to complications of chronic kidney disease and acute kidney injury, including mineral bone disease and anemia.
Keywords: HEMODIÁLISIS -- CONGRESOS; DIÁLISIS PERITONEAL -- CONGRESOS; INSUFICIENCIA RENAL CRÓNICA -- TRATAMIENTO -- CONGRESOS; INSUFICIENCIA RENAL AGUDA -- TRATAMIENTO -- CONGRESOS